2022
DOI: 10.1093/cercor/bhac289
|View full text |Cite
|
Sign up to set email alerts
|

Delay-related activity in marmoset prefrontal cortex

Abstract: Persistent delay-period activity in prefrontal cortex (PFC) has long been regarded as a neural signature of working memory (WM). Electrophysiological investigations in macaque PFC have provided much insight into WM mechanisms; however, a barrier to understanding is the fact that a portion of PFC lies buried within the principal sulcus in this species and is inaccessible for laminar electrophysiology or optical imaging. The relatively lissencephalic cortex of the New World common marmoset (Callithrix jacchus) c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
5
13
0
Order By: Relevance
“…Upon observing single- or multiunit activity at multiple sites of the array for approximately three weeks, we commenced unrestrained datalogger recordings of extracellular activity from the 96 implanted electrodes. A detailed description of these unrestrained datalogger-based recordings is presented in Wong et al (2023). Initially, neural data underwent processing with a common median filter to mitigate large movement-related artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upon observing single- or multiunit activity at multiple sites of the array for approximately three weeks, we commenced unrestrained datalogger recordings of extracellular activity from the 96 implanted electrodes. A detailed description of these unrestrained datalogger-based recordings is presented in Wong et al (2023). Initially, neural data underwent processing with a common median filter to mitigate large movement-related artifacts.…”
Section: Methodsmentioning
confidence: 99%
“…Previously published data from Wong and colleagues (2023) was included here. Activity within distinct non-overlapping task epochs was assessed using analyses of variance (ANOVA) to compare the mean discharge rates of each neuron for each condition (four spatial locations) and each task epoch (baseline, sample, delay, pre-response and post-response).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the marmosets relatively small body size, wireless equipment must be lightweight to not impede the animals' movements, 193 while at the same time, it must be designed to withstand the rigors of a 3D arboreal lifestyle. Recent studies using wireless recordings in marmosets have shown promising results, 193,195 recordings from up to 96 channels simultaneously while the marmoset is freely moving in the home cage. Employing such wireless recording technologies and combining them with wearable microphones and behavior tracking opens the door to a range of new questions related to marmoset vocal communication that were not possible even just a few years ago.…”
Section: Technical Advancesmentioning
confidence: 99%